Development of Target-Specific gRNAs for CRISPR-Cas9 Mediated Antifungal Resistance in Sweet Pepper - M Sedarshini; G Harini Shree; R D Ragavendhran; Prabhu Puniethaa; Kalpana B.; Balakrishnan Rengesh (BIO Web of Conferences)
Using CRISPR-Cas9, the gRNA for antifungal resistance to mildew diseases in Pepper species, especially Capsicum annuum, is designed. The Downey Mildew Resistance (DMR), and Enhanced Disease Resistance (EDR) genes were chosen, and the target-specific gRNA was designed with CRISPR-Cas9 methodology. The proficient gRNA and secondary structures were obtained for the chosen gRNA, along with the MIT and CFD scores. The prompt genes with low off-targets were considered for the putative homologous genes of PMR, EDR, and DMR. The gRNA for putative homologous genes of antifungal resistance genes was obtained. The highest MIT and CFD-scored gRNA were chosen, and the desired mutation in the Capsicum annuum species was expected to be produced when performed in vitro.